Gen Z Cinta Budaya Lokal melalui Pengembangan Media Budalo pada Pembelajaran Teks Deskripsi di MTs Negeri 4 Jembrana - Adila Qibtiyah, Nur (Widyadewata, 2025)
This study aims to develop and evaluate the effectiveness of an educational game-based learning media named "Budalo" for teaching descriptive texts in 7th at MTs Negeri 4 Jembrana. The media integrates the local cultural wisdom of Loloan Timur, Jembrana, into a game to enhance learning outcomes and foster cultural appreciation among Generation Z students. The research employed the ADDIE model with a mixed-method approach. Media validation results showed a feasibility score of 88.89% (very feasible). Implementation with 31 students demonstrated improved learning outcomes, with an average N-Gain score of 0.58 (moderate category). Cultural appreciation scores reached 78.1% (high category). Budalo is effective and relevant in improving students' learning achievements and cultural awareness